PENDIDIKAN PESANTREN SEBAGAI UPAYA DERADIKALISASI DI INDONESIA - Abdurrahman Hakim; Yunita Sari (IAIN Sorong, 2022)
The issue of radicalism which leads to the crime of terrorism in various countries by Westerners is oftenassociated with Islam. Violence, war, and conflict that result in death seem to be a picture that Islam is abrutal religion. The statements were made by them not without reason. The prolonged conflict in the MiddleEast and suicide bombing cases have been confirmed by the media as Muslim acts. To face this reality,defending Islam with an argument is not the best way. Therefore, there needs to be improvements, pressures,and countermeasures in the teachings of Islam itself. One solution that can be done is through education thatstill maintains the purity of the Islamic religion, namely Pondok Pesantren. Pondok Pesantren is an Islamiceducation and lecturing institution that teaches the values of Islam rahmatan lil-alamin, moderate, tolerant,balanced, and fair in Indonesia. Pondok Pesantren offers an education system that is based directly on theteachings of Islam Ahlussunah Wal Jamaah. As we know that the teachings of Islam Ahulussunah WalJamaah are contrary to radicalism.